Resuming Deceased Donor Kidney Transplantation in the COVID-19 Era: What Do Patients Want?. Issue 4 (5th March 2021) - Thind, Amarpreet K.; Beckwith, Hannah; Dattani, Rakesh; Dhutia, Amrita; Gleeson, Sarah; Martin, Paul; Ryan, Louise; Shuaib, Rishana; Svetitsky, Shuli; Dor, Frank J.M.F.; Brown, Edwina A.; Willicombe, Michelle
Abstract : Background: The rapidly evolving novel coronavirus 2019 (COVID-19) pandemic bought many kidney transplant (KT) programs to a halt. Integral to resuming KT activity is understanding the perspectives of potential transplant candidates during this highly dynamic time. Methods: From June 1 to July 7, 2020, a telephone survey of KT candidates on the deceased donor waiting list at Imperial College Renal and Transplant Centre in West London was conducted. The survey captured ongoing COVID-19 exposure risks and patients' views on waitlist (WL) reactivation and undergoing transplantation. Results: Two hundred seven responses were received. Of the respondents, 180 patients (87%) were happy to be reactivated onto the WL; with 141 patients (68%) willing to give consent to transplantation currently, while 53 patients (26%) felt unsure, and 13 patients (6%) would decline a KT. The vast majority of patients had no concerns. In the responses from those who were uncertain or who would decline a KT, concerns about COVID-19 infection and the need for reassurance from transplant units dominated. Universally patients wanted more information about COVID-19 infection risk with KT and the precautions being taken to reduce this risk. Conclusions: The majority of surveyed patients are in favor of reactivation and receiving a KT despite the ongoing COVID-19 pandemic. Reactivation of candidates cannot be assumed and should take an individualized approach, incorporating clinical risk with patient perspectives. Improved communication with KT candidates is highly requested. Abstract :